Biofilm-associated proteins: news from Acinetobacter. (December 2015) - De Gregorio, Eliana; Del Franco, Mariateresa; Martinucci, Marianna; Roscetto, Emanuela; Zarrilli, Raffaele; Di Nocera, Pier
Abstract Background A giant protein called BAP (biofilm-associated protein) plays a role in biofilm formation and adhesion to host cells inA. baumannii . Most of the protein is made by arrays of 80–110 aa modules featuring immunoglobulin-like (Ig-like) motifs. Results The survey of 541A. baumannii sequenced strains belonging to 108 STs (sequence types) revealed that BAP is highly polymorphic, distinguishable in three main types for changes both in the repetitive and the COOH region. Analyzing the different STs, we found that 29 % feature type-1, 40 % type-2 BAP, 11 % type-3 BAP, 20 % lack BAP. The type-3 variant is restricted toA. baumannii, type-1 and type-2 BAP have been identified also in other species of theAcinetobacter calcoaceticus-baumannii (ACB) complex.A. calcoaceticus andA. pittii also encode BAP-like proteins in which Ig-like repeats are replaced by long tracts of alternating serine and aspartic acid residues. We have identified in species of the ACB complex two additional proteins, BLP1 and BLP2 (BAP-like proteins 1 and 2) which feature Ig-like repeats, share with BAP a sequence motif at the NH2 terminus, and are similarly expressed in stationary growth phase. The knock-out of either BLP1 or BLP2 genes of theA. baumannii ST1 AYE strain severely affected biofilm formation, as measured by comparing biofilm biomass and thickness, and adherence to epithelial cells. BLP1 is missing in the majority of type-3 BAP strains. BLP2 is largely conserved, but is frequently missing in BAP-negative cells. Conclusions Multiple proteins sharing Ig-like repeats seem to be involved in biofilm formation. The uneven distribution of the different BAP types, BLP1, and BLP2 is highly indicative that alternative protein complexes involved in biofilm formation are assembled in differentA. baumannii strains.